The Socio-Economic Impacts After Relocation of Pasar Panjang Traders to the Wua-Wua Central Market Kendari City - Nur Asiah; Sulsalman Moita; Ratna Supiyah (Indonesian Journal of Social and Environmental Issues (IJSEI), 2020)
This study aims to determine the process of relocation of the Pasar Panjang traders to the Central Market of Wua-Wua Kendari City and to determine the impact caused after the relocation. This research uses a qualitative approach, where data is collected through observation, interview, and documentation techniques. The results of this study indicate that the relocation of Pasar Panjang traders to the Wua-Wua Central Market of Kendari City is intended for fire victims. The government provides approximately 1,200 stalls with adequate facilities. The impact caused by the relocation of the Pasar Panjang traders to the Central Market of Wua-Wua, Kendari City, includes social impacts, namely the interaction between traders is well established, some locations are not given much attention to cleanliness. While the economic impact of the lack of merchant income due to lack of visitors, most traders take capital in the bank to open a business so they do not have savings, the volume of business traders to decline.